MILLIY O’Z O’ZINI ANGLASHNING PSIXOLOGIK ASOSLARINI O’RGANISH - Amirova, G. (SCIENCE and SOCIETY, 2017)
The feeling of self-consciousness as an important category of social psychology is a specific feature beauture of every nation and it is a psychological phenomenon which is connected with its spiritual perfection. It has an important role in the life of the nation and society. Development and power of the nation is connected with the people and especially with the youth. Through the national self-consciousness of the youth-students social establishments are formed and it brings to positive actions and the deliberation of national priority.